THE ROLE OF MOTIVATIONAL INTERVIEWING TECHNIQUES IN OVERCOMING INTERFERENCE PECANDU DRUGS AT AR-RAHMAN DRUG REHABILITATION PANTI AR-RAHMAN PLAJU DARAT PALEMBANG - Neni Noviza (Polteknik Ilmu Pemasyarakatan, 2018)
One of the problems experienced by drug addicts is the loss of confidence due to the effects of consuming drugs. To overcome this one of the techniques used dip re-rehabilitation of Ar rahman drugs is to use motivational interviewing techniques. This technique aims to provide motivation for addicts to change. This study aims to determine the confidence of drug addicts when they enter the rehabilitation of drugs Ar-Rahman, to know the process of motivational techniques Interviewing (MI) in Arrangman Drug Rehabilitation and to know the role from motivational interviewing (MI) techniques. The type of data used is qualitative data. The subjects of this study amounted to 3 people drug addicts, and 1 counselor. Sources of data taken in this study are primary and secondary data sources. Data obtained by using interview methods, observation methods and documentation methods. Data analysis techniques of qualitative data analysis consists of four stages, namely: data reduction (data reduction), presentation data (display data), conclusion drawing and verification. From the research results obtained confidence drug addicts when new re-entry rehabilitation Ar-Rahman drugs that is, often solitary, be closed to others, silent, embarrassed, insecure and always negative thingking (thinking negative) to others, fear, to himself, always be negative, no matter to the environment, reluctant to communicate, not serious, irresponsible, closed and pessimistic about what he does. The process of motivational interviewing (MI) technique carried out by the counselor at Ar-Rahman drug rehabilitation center and the four principles is run, expressing empathy, developing discrepancy, accepting resistance and supporting efficacy. Motivational Interviewing Technique (MI) is very instrumental in overcoming the confidence of drug addicts with the change of attitude behavior and way of thinking, the changes experienced are, the client is more serious, responsible, think and be positive, open to others, optimistic, thinking that is rational, and better understand the feelings of self and others.